Lifecycle management in government-driven open source projects – practical framework - Henttonen, Katja; Kääriäinen, Jukka; Kylmäaho, Jani (International Journal of Information Systems and Project Management, 2022)
In many parts of the world, public sector organizations are increasingly interested in collaborating across organizational (and even national) boundaries to develop software solutions under an open licence. However, without sound lifecycle management practices, the full benefits of open collaboration are not achieved and projects fail to achieve sustained success. This paper introduces a lifecycle management model and framework for government-driven open-source projects and reports about its use in a real-life case study. Our focus is on lifecycle management activities which take place between deployment and end-of-life. The framework was developed iteratively through a series of focus group discussions with representatives of public sector organizations. After the framework had been taken into use in our real-life case project, individual qualitative interviews were conducted to collect experiences on its benefits and weaknesses. According to the initial evidence, the deployment of the framework seems to have brought concrete benefits to the project, e.g. by contributing positively to community growth, software quality and inter-organizational learning.